Factors associated with 36-month loss to follow-up and mortality outcomes among HIV-infected adults on antiretroviral therapy in Central Kenya - Paul Wekesa; Angela McLigeyo; Kevin Owuor; Jonathan Mwangi; Evelyne Nganga; Kenneth Masamaro (BMC, 2020)
Abstract Background The scale-up of HIV treatment programs has resulted in a reduction in HIV-related morbidity and mortality. However, retention of patients in these programs remains a challenge in sub-Saharan Africa. Understanding factors associated with loss to follow-up (LTFU) and mortality outcomes is therefore important to inform targeted program interventions. Methods A retrospective multi-cohort analysis of 23,890 adult patients on ART over 36 months of follow-up in Kenya was done. Multivariate logistic regression analysis was done to assess for factors associated with LTFU and mortality at 6, 12, 24, and 36 months of follow-up. Results Majority, 67.7%, were female. At 36 months, 27.2% were LTFU and 13.5% had died. Factors associated with mortality at 36 months included older age (51 years and above) using 20-35 years as reference [(adjusted odds ratio [aOR], 1.51, 95% confidence interval (CI) 1.23-1.86, p < 0.001], being male (aOR, 1.59, 95% CI 1.39-1.83, p < 0.001), divorced using married as reference (aOR, 1.86, 95% CI 1.56-2.22, p < 0.001), having a body mass index (BMI) score of less than 18.5 kg/m2 using 18.5-24.9 kg/m2 as reference (aOR = 1.79, 95% CI 1.52-2.11, p < 0.001), and, World Health Organization stage III and IV using stage I as the reference (aOR, 1.94, 95% CI 1.43-2.63 and aOR, 4.24, 95% CI 3.06-5.87, p < 0.001 respectively). Factors associated with LTFU at 36 months included being young between 20 and 35 years (aOR, 1.49, 95% CI 1.40-1.59, p < 0.001) using 36-50 years as reference, being male (aOR, 1.19, 95% CI 1.12-1.27, p < 0.001), and being single or divorced using married as reference (aOR, 1.34, 95% CI 1.23-1.45 and aOR, 1.25, 95% CI 1.15-1.36, p < 0.001 respectively). Patients with baseline BMI of less than 18.5 kg/m2 using normal BMI as reference (aOR, 1.68, 95% CI 1.39-2.02, p < 0.001) were also likely to be LTFU. Conclusions Factors associated with LTFU and mortality were generally similar over time. Implementation of programs in similar settings should be tailored to gender, age profiles, nutritional, and, marital status of patients to address LTFU. In addition, programs should focus on the care of older patients to reduce the risk of mortality.